The Effectiveness Of The Pre-School Transition Program / Wan Noor Ashikin Wan Abdullah - Wan Abdullah, Wan Noor Ashikin (2002)
The Year One Pre-School Transition Program is a program that was developed in order to help the pupils to adapt themselves from informal education at their home or kindergarten to a more formal education in Year One of primary school. This program was launched in January 2001 and it is hoped to change the patterns of usual teaching and learning activities done by the Year One teachers before, therefore new techniques, activities and notions were set-up for the teachers to carry them out through this program. As the program was newly launched, and with the hope that the stated objectives can be achieved by the end of March, the program should be as effective as it is expected to be. Through this research, based on the opinions and views from the involved teachers, the objectives were impossible to be achieved as there were many weaknesses occurred before and during the program. This research highlights on how important for the teachers to be well prepared with enough information and training before conducting any programs or activities. No matter how good the program or the activity is, it wouldn’t work out if the facilitators or the teachers are unprepared physically and mentally.